Minoxidil Skin Delivery from Nanoemulsion Formulations Containing Eucalyptol or Oleic Acid: Enhanced Diffusivity and Follicular Targeting - Eman Abd; Heather A. E. Benson; Michael S. Roberts; Jeffrey E. Grice (MDPI AG, 2018)
In this work, we examined enhanced skin delivery of minoxidil applied in nanoemulsions incorporating skin penetration enhancers. Aliquots of fully characterized oil-in-water nanoemulsions (1 mL), containing minoxidil (2%) and the skin penetration enhancer oleic acid or eucalyptol as oil phases, were applied to full-thickness excised human skin in Franz diffusion cells, while aqueous solutions (1 mL) containing minoxidil were used as controls. Minoxidil in the stratum corneum (SC), hair follicles, deeper skin layers, and flux through the skin over 24 h was determined, as well as minoxidil solubility in the formulations and in the SC. The nanoemulsions significantly enhanced the permeation of minoxidil through skin compared with control solutions. The eucalyptol formulations (NE) promoted minoxidil retention in the SC and deeper skin layers more than did the oleic acid formulations, while the oleic acid formulations (NO) gave the greatest hair follicle penetration. Minoxidil maximum flux enhancement was associated with increases in both minoxidil SC solubility and skin diffusivity in both nanoemulsion systems. The mechanism of enhancement appeared to be driven largely by increased diffusivity, rather than increased partitioning into the stratum corneum, supporting the concept of enhanced fluidity and disruption of stratum corneum lipids.